Effect of daily light integral treatments on free amino acids and sugars contributing flavor and acrylamide formation in potato tubers of Solanum tuberosum L. - Rotola-Pukkila Minna K.; Välimaa Anna-Liisa; Suomela Jukka-Pekka; Yang Baoru; Karhu Saila; Hopia Anu I. (SCIENTIFIC AGRICULTURAL SOC FINLAND, 2022)
To study the effect of photoperiodic conditions on the chemical composition of potato tubers, seven cultivars, grown under controlled conditions, were evaluated for the content of free amino acids (FAA) and sugars. The differences in these compounds may have an effect on the susceptibility of acrylamide formation during potato processing as well as on the flavor profile of potato products. Tubers were produced in growth chambers under two artificially induced photoperiods; 8 h light and 15 h light per day, resulting in conditions with two different daily light integral (DLI) levels. The photoperiodic treatments influenced the total FAA and free sugar contents and composition. Of the analyzed 19 FAAs, the concentrations of 14 FAAs were significantly lower in tubers exposed to the 15 h light period compared to 8 h light, whereas the glucose content was significantly higher. The total FAA concentrations were 15-46% lower and the glucose concentrations 6-64% higher in the seven cultivars exposed to the 15 h light conditions than in those grown in 8 h light.